2022
DOI: 10.1002/ece3.8526
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A expression in freshwater fish of western New York as an indicator of pollution levels

Abstract: Various species of freshwater fish regulate the expression of certain proteins in response to environmental contamination. Previous research has shown that CYP1A expression increases in response to contaminant levels and can result in increased tumor formation. Fish in contaminated environments would thus benefit by downregulating the expression of CYP1A to reduce tumor prevalence as an adaptive strategy. Alternatively, monitoring of the CYP1A protein in fish can serve as a bioindicator of the pollution level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…More research is needed to investigate the interactions among individuals within a population and their impact on a species' overall adaptive capacity. Recent studies have shown that certain genes in fish alter their expression profiles in response to pollution, such as CYP1A expression, which can lead to tumour formation 9 . Local adaptation, which results in genetic modifications at the genome level, can also contribute to an organism's ability to survive.…”
Section: Introductionmentioning
confidence: 99%
“…More research is needed to investigate the interactions among individuals within a population and their impact on a species' overall adaptive capacity. Recent studies have shown that certain genes in fish alter their expression profiles in response to pollution, such as CYP1A expression, which can lead to tumour formation 9 . Local adaptation, which results in genetic modifications at the genome level, can also contribute to an organism's ability to survive.…”
Section: Introductionmentioning
confidence: 99%